Effect of Eucheuma cottonii extract on interleukin-1 level and caspase-3 expression in borax-induced rat’s hepatocyte - Muhyi, Ahmad; Wibowo, Joko Wahyu; Priyantini, Sri (Faculty of Medicine, Universitas Islam Sultan Agung (UNISSULA), Indonesia, 2022)
Borax is a hepatotoxic substance and induces oxidative stress in hepatocytes. It may trigger the expression of pro-inflammatory cytokines like Interleukin-1 and apoptotic signals like Caspase-3. Extract of the seaweed Eucheuma cottonii contains carotenoids and flavonoids which suppress oxidative stress in hepatocyte. This study was conducted to determine the effect of E. cottonii extract on borax-induced Interleukin-1 and Caspase-3 expression in rat hepatocyte cells. This research employs a posttest-control group design. Twenty Wistar male rats were separated into four groups: control group (K1) received no intervention, K2 received Na-CMC 0.5% for 17 days and Borax 40 mg/200 g on the fourth day every hour for 14 days, P1 and P2groupsÂ were administered E. cottonii extracts at doses of 600 mg/200 g and 1200 mg/200 g for 17 days, respectively, followed byborax induction at a dose of 40 mg/200 g on the fourth day with a one-hour interval for 14 days. Interleukin-1 (IL-1) levels were measured with ELISA, while caspase-3 expression was measured with PCR. For the statistical analysis, Kruskal Wallis and Mann Whitney were used. The level of IL-1 in P2 was significantly lower than in K2 (p<0.05). Caspase-3 expression was significantly lower in P1 and P2 than in K2 (p<0.05). IL-1 level and caspase-3 expression of hepatocytes are affected by administration of E. cottonii extract. The extract has the ability to prevent inflammation and hepatocyte apoptosis.<img src=